Autoantibodies: Focus on anti-DNA antibodies - Almqvist, Nina; Winkler, Thomas; Mårtensson, Inga Lill (Self/Nonself - Immune Recognition and Signaling, 2011)
Ever since the days of Ehrlich and the birth of humoral immunity, self-reactivity or 'horror autotoxicus' as referred to by Paul Ehrlich, has been of great concern. For instance, in patients with the autoimmune disease systemic lupus erythematosus (SLE), anti-nuclear and anti-DNA antibodies have been recognized for many years. Despite this, the exact mechanism as to how the immune system fails to protect the individual and allows these autoantibodies to develop in this and other systemic autoimmune diseases remains uncertain. So how can we explain their presence? Evidence suggests that B cells expressing autoreactive antibodies do not normally arise but rather undergo negative selection as they develop. In light of this, it might seem contradictory that not all autoreactive B cell clones are eliminated, although this may not even be the intention since autoantibodies are also found in healthy individuals and may even protect from autoimmunity. Here, we will discuss autoantibodies, in particular those recognizing DNA, with regard to their reactivity and their potentially pathogenic or protective properties. © 2011 Landes Bioscience.
Keywords: Anti-DNA antibodies; Anti-nuclear antibodies; Anti-nucleosome antibodies; Autoantibodies; B cell receptors; B cells; CDR3; Natural antibodies; SLE; Systemic autoimmunity